Risco operacional: o cálculo do capital regulatório usando dependência - Gonçalves, Débora Delbem (2014)
In this paper we propose a new method for the calculation of regulatory capital required for operational risk. This method is based on some important assumptions for calculation of this capital, for instance, expert opinion, dependence between loss variables considering the joint probability associated to two loss events. The copula theory is applied to determine this joint probability. Furthermore, we present two more methods, sum method proposed by Basel II Accord (2004) and non-perfect correlation method proposed by Frachot et al. (2004). Finally, we perform a simulation studies in order to compare all the methods presented in this dissertation.